The Canadian Labor Market : Developments, Prospects, and Policy - Prasad, Eswar (IMF Working Papers; Working Paper ;, 1994)
This paper examines recent developments in the Canadian labor market. Using disaggregated labor market data, various hypotheses concerning the slow employment growth and rise in unemployment since 1990 are evaluated. The analysis indicates that a large part of the recent rise in the unemployment rate may reflect an increase in the structural rather than the cyclical component of unemployment. Various sources of labor market rigidities that may have contributed to the increase in structural unemployment are examined. In particular, the role of the unemployment insurance system in contributing to labor market rigidity and measures for reforming this system, including the recent proposals of the government, are discussed. Finally, this paper examines active labor market policies that could help to alleviate structural unemployment.